Bravery and Boundaries: A Feminist Critique of Patriarchal Norms and Gender Roles In Brave - Chang, Gabrielle Angela; Hutahayan, Regine Juliana Leonora; Elaine, Janette; Sabbathany, Meicy; Jeswin, Oliver Rafael (Jurnal Pendidikan Makarios, 2026)
This research examines “Brave” through the lens of feminist literary criticism, by using Gender Trouble (1990) by Judith Butler, it focuses on how the story addresses gender roles in patriarchal society and a mother daughter relationship, exploring the role of women in ‘Brave’ society. As a result 1) Traditional gender roles are being forced therefore limiting women's freedom and reinforcing patriarchal authority. In this film Merida's behavior and actions do not follow the traditional gender roles or what they expected her to be, she was challenging it. 2) The conflict between Elinor and Merida shows how traditional gender roles are passed down through generations. Elinor pushes tradition but Merida wants freedom, so this limits Merida’s choices and identity. 3) Merida's leadership style represents her willingness to have freedom and choose her own path. She also showed that she is brave to express her thoughts and feelings. These elements reflect the expectations that society expects women to be. This also shows that women have to be brave to get their freedom. This is important to encourage women and young audiences to understand about gender, identity, and power. We hope that future researchers can explore other animated films that portray resistance to gender norms and a conflict between mother and daughter.